Improved of Mechanical Characteristics of Gargar Mud by Mineral Additives - Benhadj Ziane Mokhtari, Fouzia; Youcefi, Abdelkader; Driss, Abdelmoumen Aala Eddine; Ghrici, Mohamed (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The operational dams in Algeria lose 32 million m3 of water storage capacity each year, and fifteen of these dams are threatened by siltation. This investigation forms a component of a management strategy for dredged silt in the Gargar Dam, the third-largest dam in Algeria with considerable sedimentation.
Keywords: Gargar dam; mud; dredge sediment; lime; pozzolana